CREATIVITY AND INNOVATION IN THE FASHION BUSINESS contemporary issues in fashion design and... product development. - Goworek, Helen; Bailey, Fiona (ROUTLEDGE, 2024)
Creativity and Innovation in the Fashion Business explores the ways in which creativity and innovation play a central role across the fashion industry, paying particular attention to design and technical perspectives. This topic is examined through careful theoretical analysis, incorporating the perspectives of multiple contributors who together possess a wealth of combined experience in creative and technical roles in the fashion business. Broad in scope, this textbook first provides a wide overview of creativity and innovative developments across the industry, before considering technical and digital innovation in production and product development, as well as trend forecasting. The final part of the book then consists of an exploration of sustainable innovation in design for fashion brands and retailers. Each chapter includes aims and summaries to structure learning and highlight key points, academic insights from thought leaders and interviews from industry and academia. A vital introductory textbook, Creativity and Innovation in the Fashion Industry is well-suited to undergraduate and postgraduate modules across subjects such as Fashion Business, Fashion Design and Manufacturing, Product Development, Innovation Management, and Buying and Merchandising. Online resources include PowerPoint slides and a test bank.
Keywords: Clothing trade -- Technological innovations.; Clothing trade -- Management.; Creative ability in business.; elektronické knihy; electronic books